Non-pharmacological therapies applied in pregnancy and labor: an integrative review - Camilla Benigno Biana; Diana Cecagno; Adrize Rutz Porto; Susana Cecagno; Vanessa de Araujo Marques; Marilu Correa Soares (SciELO, 2021)
ABSTRACT Objective: To identify non-pharmacological therapies applied during pregnancy and labor. Method: Integrative review conducted in the databases: PubMed, ScieLO and PEDro, searching for articles from 2008 in English, Spanish and Portuguese. The descriptors used were: pregnancy, childbirth, physiotherapy, alternative and complementary medicine, alternative therapy, non-pharmacological therapy, biomechanical therapy. Results: Forty-one articles were analyzed and subdivided into ten categories of nonpharmacological therapies: massage, perineal massage, hot bath, supportive care, childbirth preparation group, breathing techniques, pelvic floor exercises, transcutaneous electrostimulation, Swiss ball and spontaneous pushing. Six articles (60%) showed a positive outcome for reduction of pain in labor and all of them had a positive outcome for different variables of labor, such as reduction of time, anxiety and pelvic floor laceration rates. Conclusion: The use of non-pharmacological therapies was efficient to reduce the effects of labor and childbirth, such as pain, duration of labor, anxiety, laceration and episiotomy.